STS goes to school: Spatial imaginaries of technology, knowledge and presence - Sørensen, Estrid (Outlines. Critical Practice Studies, 2007)
The following text presents a revised and extended version of the public defence of my Ph.D. thesis, which I presented at the Faculty of Social Sciences on 18th November 2005, Copenhagen University. The thesis applies and develops theoretical perspectives from Science and Technology Studies – especially Actor-Network Theory – on the empirical field of primary education. This field has not prior been approached by these theories. Based on ethnographic field studies the thesis presents and compares what I call spatial imaginaries of interactions of humans and learning materials in a traditional classroom and in a computer lab. The study describes and discusses the forms of knowledge and the forms of presence performed through these socio-material interactions. The study thus contributes a definition of materialities that takes the understanding of technology in education beyond the dominant humanist approach to schooling.